Effects of phosphate neutralization on the shape of the AP-1 transcription factor binding site in duplex DNA. - Tomky, L A (1998)
Previous electrophoretic experiments suggest that the AP-1 site in duplex DNA bends in response to the pattern of amino acid charges distal to the basic region in bound bZIP proteins. The extent and direction of apparent DNA bending are consistent with the prediction that DNA will collapse locally upon asymmetric phosphate charge neutralization. To prove that asymmetric phosphate neutralization could produce the observed degree of DNA bending, the present experiments partially substitute anionic phosphate diesters in the AP-1 site with various numbers of neutral methylphosphonate linkages. DNA bending is induced toward the neutralized face of DNA. The degree of DNA bending induced by methylphosphonate substitution (approximately 3.5 degrees per neutralized phosphate) is comparable to that induced by GCN4 variants carrying increasing numbers of additional basic amino acids. It is plausible, therefore, that asymmetric phosphate neutralization is the cause of DNA bending in such complexes.